Medieval exegesis and religious difference : commentary, conflict, and community in the premodern Mediterranean - Szpiech, Ryan (Bordering religions., 2015)
Jews, Christians, and Muslims all have a common belief in the sanctity of a core holy scripture, and commentary on scripture (exegesis) was at the heart of all three traditions in the Middle Ages. At the same time, because it dealt with issues such as the nature of the canon, the limits of acceptable interpretation, and the meaning of salvation history from the perspective of faith, exegesis was elaborated in the Middle Ages along the faultlines of interconfessional disputation and polemical conflict. This collection of thirteen essays by world-renowned scholars of Judaism, Christianity, and I.